Infertility treatment for Chinese women with P450 oxidoreductase deficiency: Prospect on clinical management from IVF to FET - Li, Yan; Zhang, Cui-Lian; Zhang, Shao-Di (Frontiers in Endocrinology, 2022)
Cytochrome P450 oxidoreductase deficiency (PORD) is a rare recessive disease with multiple clinical manifestations, which is usually diagnosed in neonates and children because of ambiguous genitalia or skeletal malformations. Moreover, the paucity of studies does not allow us to establish whether adult-onset PORD is associated with infertility. Here, we report clinical and laboratory findings in two phenotypically normal women diagnosed with PORD who underwent in vitro fertilization (IVF) and frozen embryo transfer (FET). We modified the gonadotropin stimulation protocol during controlled ovarian hyperstimulation (COH) and suggest the use of the vaginal 17β-estradiol route for endometrium preparation in hormone replacement therapy (HRT) cycles. We presume that PORD may be associated with infertility in several aspects, including disordered steroidogenesis, endometrium impairment, attenuation of drug metabolism, and the high risk of miscarriage. Our observations will help the early diagnosis and make a tailored approach to infertility management in adult-onset PORD.